Sustainable Growth and Liquidity on Profitability: A Study on Mining Sector Companies Listed at Indonesia Stock Exchange in 2018 - Shekinah Manullang; Francis Hutabarat (Politeknik Negeri Madiun, 2020)
The study projected to determine the effect of sustainable growth & liquidity on profitability, sustainable growth on profitability, and liquidity on profitability. Data derived are quantitative from IDX companies financial statement in 2018. The sample is 43 companies of IDX mining sector companies. The variables used in this study are sustainable growth and liquidity as independent variables. Profitability as the dependent variable. The research analysis uses statistical data that is descriptive statistics, correlation matrix, significant tests, regression analysis for research data in the mining sector. Test results show that the effect is significant between sustainable growth rate and liquidity on profitability. And the effect between Liquidity on Profitability is not significant. Simultaneously states there is a significant influence between sustainable growth rate and Liquidity on the profitability of mining companies in the Indonesia stock exchange in 2018.